Ancient Semiotics and its Influence on Formation of Topic of Signification - Amin Shahverdi (حکمت و فلسفه, 2019)
In this paper, the formation and development of Signification theory and its effect on Muslim thinkers are studied. In the ancient period, there were three important schools that investigated signals and issues surrounding them. First, Aristotle investigated signs at the outset of his “On Interpretation”, as well as, at the end of his “Prior Analytics”. Second, physicians with classifying signs into two main groups made various comments about the argumentative role of them in inferences. Third, Stoics studied signs as a primary part of their logic and investigated arguments on the basis of them. In the Islamic period, Avicenna is the first logicians studying verbal signification meticulously and classifying it into three parts. Avicenna’s doctrines about verbal signification which are repeated in other logicians’ books are in accordance with Aristotle’s discourse at the beginning of “On Interpretation”. Natural verbal signification is added into logical books explicitly by Fakhr al-Dīn al-Rāzī and after him, Afḍal al-Dīn al-Khūnajī and other logicians implied to it. Rational verbal signification is added to verbal signification in the works of Siraj al-Dīn Urmawī, Allameh Ḥelli, and Quṭb al-Dīn Shirāzī. Furthermore, Quṭb al-Dīn Rāzī with examining non-verbal signification extended the domain of signification theory, as well as he introduced a new definition of signification. This new definition of signification and attention to non-verbal signification possibly are rooted in Aristotle’s comment in the second book of Prior Analytics as well as Stoics and physicians' doctrines which were transmitted through theologians and Aristotle commentator into later logicians.